Grazing by non‐native ungulates negatively impacts vegetation important to a native species of concern - Phillip A. Street; Levi Jaster; Thomas E. Dilts; Tessa L. Behnke; James S. Sedinger (Ecosphere)
Abstract Non‐native grazers compete with native species across the globe. We present a novel approach to study the composition of the herbaceous understory across three study areas within the Great‐Basin with different historic and contemporary grazing regimes. We surveyed the landscape using distance sampling for livestock and horse feces as an index of use. In addition, we surveyed the herbaceous understory of random sites as well as sites chosen by female Greater sage‐grouse to nest and brood their chicks. We used a novel Bayesian hierarchical modeling framework to link vegetation metrics with the spatial–temporal distribution of horses and livestock while accounting for observation error. When livestock and feral horses were not present, we found that Greater sage‐grouse use sites with higher percentages of perennial grasses and forbs to build their nests and brood their chicks compared with what was available to them. As livestock increased, we found evidence for decreases in the percentage of perennial grasses, forbs, cheatgrass (Bromus tectorum), and increases in the amount of bare ground. These effects were consistent at available sites and brood sites; however, we found less evidence for an impact of livestock at nest sites. As feral horses increased, we observed similar results at available sites, but at sites chosen by females to nest and brood their chicks, we observed increases in the amount of invasive cheatgrass as feral horses increased, which could reflect attempts by Greater sage‐grouse to compensate for reductions in protective cover. We present a noninvasive approach to assess space use that can be applied to other species. More importantly, we document that grazing by non‐native ungulates impacts components of the plant community important to Greater sage‐grouse reproduction. We provide spatial–temporal maps of livestock and feral horse use to aid managers attempting to balance the needs of livestock producers, feral horses, Greater sage‐grouse, and ecosystem function.